Fluorophotometric Measurement of Corneal Autofluorescence in Diabetic and Normal Eyes - Srinivasan, Ramyaa; Bhandari, Madhavendra; Sharma, Tarun; Raman, Rajiv (Nepalese Journal of Ophthalmology, 2020)
Introduction: Corneal autofluorescence (AF) has been recommended as an indicator of diabetic retinopathy. This study was conducted to evaluate corneal autofluorescence in non-insulin dependent diabetes subjects (with and without diabetic retinopathy) and compare the changes with healthy subjects. Materials and methods: In this cross-sectional study, 145 eyes of diabetes mellitus subjects with and without diabetic retinopathy and 34 eyes of normal healthy subjects were included. Diabetic patients were subdivided by the severity of retinopathy based on international clinical diabetic retinopathy disease severity scale. The investigations included fluorophotometric determination of corneal autofluorescence, fasting glucose level (FBS) and glycosylated hemoglobin (HbA1c). Results: The corneal autofluorescence values were significantly higher in moderate NPDR, severe NPDR and PDR when compared with healthy subjects (p<0.001). FBS values and HbA1c were significantly higher in all diabetic groups than the healthy subjects (p<0.001). In linear regression test, corneal autofluorescence seem to be related to duration of diabetes and FBS, but not with age and HbA1c. Conclusion: We conclude that the level of corneal autofluorescence is dependent on the severity of diabetic retinopathy. Our study suggests that the formation of autofluorescent products in cornea depend upon the glucose concentration in the aqueous humor.